Female glucagon receptor knockout mice are prone to steatosis but resistant to weight gain when fed a MASH‐promoting GAN diet and a high‐fat diet - Katrine D. Galsgaard; Emilie Elmelund; Jenna E. Hunt; Mark M. Smits; Trisha J. Grevengoed; Christina Christoffersen; Nils J. Færgeman; Jesper Havelund; Nicolai J. Wewer Albrechtsen; Jens J. Holst (Physiological Reports)
Abstract Glucagon is secreted from the pancreatic alpha cells and regulates not only hepatic glucose production, but also hepatic lipid and amino acid metabolism. Thus, glucagon provides a switch from hepatic glucose and lipid storage towards lipid and amino acid breakdown fueling glucose production during fasting. However, the effects of genetic deletion of the glucagon receptor on lipid metabolism are unclear. We therefore assessed parameters of lipid metabolism in fasted and non‐fasted male and female mice with permanent whole‐body deletion of the glucagon receptor (Gcgr−/− mice). To investigate whether Gcgr−/− mice tolerated a diet promoting metabolic dysfunction‐associated steatohepatitis (MASH) and steatosis, we fed female Gcgr−/− mice the Gubra Amylin Nonalcoholic steatohepatitis (GAN) diet and high‐fat diet (HFD), respectively. We found that non‐fasted Gcgr−/− mice fed standard chow showed hypercholesterolemia and increased liver fat (borderline significant in non‐fasted male Gcgr−/− mice, but significant in the remaining groups). In the fasted state these changes were insignificant due to fasting‐induced steatosis. When challenged with a GAN diet and HFD, female Gcgr−/− mice were prone to steatosis and dyslipidemia but resistant to weight gain. Taken together, our data highlight glucagon as an important physiological regulator of not just glucose, but also hepatic lipid metabolism.